Optimization of Public Services of State Civil Services in Human Resource Management Perspective in Poso Regional Public Hospital (RSUD) - Suwardhi Pantih; Syahir Natsir; Idris Idris; Harnida Wahyuni Adda (Budapest International Research and Critics University, 2021)
This study aims to determine the optimization of public services for the State Civil Apparatus (ASN) from the perspective of human resource management and the supporting and inhibiting factors in the Poso Regional General Hospital. This type of research is qualitative research. The results showed that transparency is open, easy to understand and accessible to all parties who need it and is provided adequately and easily understood. This dimension is felt by the community who uses the service as good, so the community evaluates it well and feels the satisfaction of the services provided. Transparency affects the service process in order to create a good impression so that the ultimate goal of satisfaction can be achieved. This dimension of accountability is the ability to provide services in a timely and consistent manner, service standards and promised times that can be accounted for. Conditional, namely the responsiveness of the apparatus in providing the services needed and being able to complete the service quickly according to the promised time period with the conditions and capabilities of the service provided by the officer. This condition situation is related to the reason and way of thinking of the apparatus shown to the customer. Participation encourages community participation in service delivery by taking into account the aspirations, needs and expectations of the community. The guarantee dimension includes knowledge, ability, politeness and trustworthiness possessed by the apparatus, free from dangers, risks, and doubts that result in disturbances in the normal structure of life. Providers and recipients of public services must fulfill the rights and obligations of each party. The inhibiting factor is the lack of apparatus resources, the lack of infrastructure and infrastructure. The supporting factors are encouraging each other's apparatus, holding coordination or evaluation meetings every three months and then giving the planting of awareness to serve the community sincerely and according to conscience.